2015
DOI: 10.1080/21592799.2015.1086501
|View full text |Cite
|
Sign up to set email alerts
|

Arf-like GTPase Arl8: Moving from the periphery to the center of lysosomal biology

Abstract: These authors equally contributed to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 58 publications
1
66
0
Order By: Relevance
“…It remains however puzzling, that the lysosomal kinesin adaptor Arl8 localizes to the second BRP positive subfraction of early precursors as it might be expected to be component of the VGlut/LAMP1 carrying early precursors. A possible, simplistic interpretation could be that although primarily described as a regulator of lysosome and lysosome related organelle mobility (Khatter et al, 2015;Rosa-Ferreira and Munro, 2011) the elementary function of Arl8 would comprise of the directional movement of organelles with a lysosomal membrane identity, thus including, next to conventional lysosomes also mature presynaptic precursors, possibly also including SV precursor described in C.elegans (Klassen et al, 2010), where Arl8 was shown to affect SV precursors trafficking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It remains however puzzling, that the lysosomal kinesin adaptor Arl8 localizes to the second BRP positive subfraction of early precursors as it might be expected to be component of the VGlut/LAMP1 carrying early precursors. A possible, simplistic interpretation could be that although primarily described as a regulator of lysosome and lysosome related organelle mobility (Khatter et al, 2015;Rosa-Ferreira and Munro, 2011) the elementary function of Arl8 would comprise of the directional movement of organelles with a lysosomal membrane identity, thus including, next to conventional lysosomes also mature presynaptic precursors, possibly also including SV precursor described in C.elegans (Klassen et al, 2010), where Arl8 was shown to affect SV precursors trafficking.…”
Section: Discussionmentioning
confidence: 99%
“…We recently found that presynaptic precursors possess a lysosomal membrane identity as they acquire lysosomal membrane proteins, but are devoid of the lysosomal peptidase cathepsin, in a hitherto unexplained maturation process, hence the term PLVs for presynaptic lysosome-related vesicles, before being axonally transported via the small Arf-like GTPase Arl8 (Vukoja et al, 2018). Arl8 is an evolutionary conserved adaptor for kinesin motor proteins implicated in the anterograde transport of lysosomes and lysosome-related organelles (Khatter et al, 2015;Rosa-Ferreira and Munro, 2011) and a similar Arl8-dependent mechanism regulates axonal SV precursor trafficking in C. elegans (Klassen et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These proteins interact with each other and link lysosomes to microtubules for their transportation to the ruffled border during bone resorption (Supplemental Figure 17F). Elucidation of PLEKHM1 and its interacting proteins provides insights not only into osteoclast biology, but in lysosome biology as well, especially in the quickly expending field of lysosome positioning (50)(51)(52)(53)(54)(55)(56)(57)(58). Moreover, the bone-specific phenotype of mice with germline and conditional Plekhm1 deficiency suggests that PLEKHM1-mediated lysosome secretion may be a new therapeutic target for bone diseases with increased resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Late endosome (LE) and lysosome motility and their fusion with other compartments are regulated by action of two small GTPases, Rab7 and Arl8b, and their numerous effectors, including adaptors, tethering factors, and microtubule-based motor-binding proteins (Wang et al, 2011;Khatter et al, 2015b). As with other members of the Rab and Arf-like (Arl) family, Rab7 and Arl8 cycle between inactive (GDP-bound) cytosolic and active (GTP-bound) membrane-bound conformations, recruiting their effectors to lysosomes in their GTP-bound state to mediate downstream functions.…”
Section: Introductionmentioning
confidence: 99%